Bilousenko P. I. , Boyko L. P. Word forming types of pluralia tantum nouns in the old russianukrainian language of XI-XIII centuries - Bilousenko P. I.; Boyko L. P. (Philological Treatises, 2020)
The paper reveals the origin of nouns pluralia tantum as a result of lexicalization of grammatical forms of plural noun, that was reflected in the shift of lexical meaning, where if used in plural, a noun denotes grammatical plurality of uniform items and parallel a single object that has a slightly different semantics or set of similar items, and because of that, pluratives that lost consequentially their singularity were formed. Amongst these substantives, there are many those that had word forming structure, and word building suffix began to be perceived as the means of creating pluratives. These processes appeared in the Old Slavic Language and continued in the Old Russian-Ukrainian by the singular inherited by models using different formants, bypassing processes of lexicalization of grammatical plural forms. The paper describes lexical and word building nouns with different types of formants. With suffixes -ане (-‟ане)/-аны/(-‟аны) in the old written memos the majority are the names of the persons based on the common and personal names of habitat (пол"не, древл"не, бужане, галичаны). After the acceptance of Christianity, a large number of branches of the faith, heresy, which contributed to the emergence of many titles that were created from nouns with this suffix (авди"не, адамане, донаит"не, монти"не). Along with them such suffixes as -ити (ангелити, николаите, оригоните), -ци (ангеловци, братници, кононовци), -ины (попузины), took place in word forming, that yield performance of suffix -ане (-‟ане)/-аны/(-‟аны). Pluralia tantum nouns with other meaning were formed with suffixes -ане (-‟ане)/-аны/(-‟аны), -ци, ины (titles of supporters of philosophical doctrines (пифагоряне, платоняне, пллатонци), titles of holidays and ceremonies (девятины, именины), tools (ножьницh, носилиці), etc. Specific meaning were pluratives with suffix –ощи, four forms of ablative with the meaning of reason. language. Discovered in the memos of XI-XIII centuries, pluralia tantum nouns were created mainly